The Side Effects of Shadow Banking on Banks’ Liquidity Provision - Paligorova, Teodora; Santos, João A C (The Review of Corporate Finance Studies, 2026)
Abstract The presence of shadow banks in corporate term loan syndicates adversely affects credit lines’ liquidity provision, despite shadow banks not directly funding credit lines. Within the same syndicated loan deal, shadow banks attract not only riskier borrowers but also fewer banks as co-lenders, both in the term loan and in the credit line. Furthermore, credit lines in deals funded by shadow banks, compared to those without shadow bank participation, are smaller, with shorter maturities, and lower drawdown rates. Overall, our results highlight that syndicated loan deals with a strong presence of shadow banks offer borrowers lower liquidity protection. JEL G21, G22, G23